Digital technology and its impacts on the sleep quality and academic performance during the pandemic - Cabral, Luana Guimarães Lima; Queiroz, Taynara Nunes; Pol-Fachin, Laércio; Santos, Adriana Rodrigues Libório dos (Arquivos de Neuro-Psiquiatria, 2022)
Background Sleep deficits caused by the overuse of digital technology is observed among medical students. Due to the coronavirus disease 2019 (COVID-19) pandemic, an emergency remote teaching method was put into practice, which may have resulted in changes in the sleep-wake cycle. The balance between the influences of external and internal synchronizers can be affected by sudden alterations in daily life, including changes in nightly habits and sleep quality, which can lead to increased levels of anxiety and reduced functional performance, for example.Objective To understand the relationship between the use of digital technology, changes in the circadian cycle, and academic performance during the pandemic.Methods The present is an analytical, cross-sectional, observational study in which a sample of 123 medical students filled out an online questionnaire on self-perception regarding sleep quality and academic performance before and during the pandemic.Results Assessing changes in sleep quality and productivity, the study revealed that 100% of the students made continuous use of screens before bedtime. Thus, during the period of social distancing and remote classes, 77.2% of the students reported “poor” or “very poor academic performance, which was probably related to the fact that 65.9% of these students were unable to maintain their productivity due to daytime sleepiness.Conclusions The prolonged use of screens was associated with poor sleep quality and changes in academic performance, with significant psychological impact. Thus, it is worth emphasizing the importance of sleep hygiene in light of the new forms of teaching implemented during the COVID-19 pandemic.
Keywords: Students, Medical; Circadian Rhythm; Academic Performance; Digital Technology; Emergency Remote Teaching